Upaya Meningkatkan Kualitas Hafalan dan Bacaan Al-Qur’an: Seminar Motivasi, Metode Cepat Menghafal, dan Pembinaan Tajwid Tahsin - Herlina Herlina; Asep Nuhdi; Ahmadi Usman; Maturidi Maturidi; Arzeti Akmalia Putri; Astria Darlis; Lufi Lutfiah; Marzul Fuardi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This activity was carried out as part of the community service program aimed at strengthening the religious and educational aspects of the students at Maahad Tahfiz Arabic Al-Gontory Lil Banat. The program consisted of three main sessions: a motivation seminar for Qur’an memorizers, the introduction of a fast memorization method, and a Tajwid–Tahsin session. The motivation seminar was designed to inspire students to develop consistency and sincerity in memorizing the Qur’an. The fast memorization method provided practical techniques to improve the effectiveness and efficiency of memorization. Finally, the Tajwid–Tahsin session emphasized the importance of accurate pronunciation and correct application of Qur’anic recitation rules. The outcome of this program showed increased enthusiasm among students in memorizing the Qur’an, better awareness of memorization strategies, and improvements in the quality of recitation. This activity is expected to support the students in achieving stronger memorization and a more accurate and beautiful recitation of the Qur’an.